2023
DOI: 10.20473/amnt.v7i1.2023.139-146
|View full text |Cite
|
Sign up to set email alerts
|

Studi Literatur: Pengaruh Diet Mediterania terhadap Profil Lipid dan Glukosa Darah Puasa pada Orang Overweight atau Obesitas

Abstract: Latar Belakang: Riset Kesehatan Dasar tahun 2018 menyatakan prevalensi obesitas di Indonesia mencapai 21,8%. Overweight dan obesitas merupakan salah satu faktor risiko terjadinya berbagai macam masalah kesehatan, diantaranya adalah dislipidemia dan diabetes mellitus tipe 2 sehingga diperlukan perbaikan gaya hidup, salah satunya dengan modifikasi diet. Diet Mediterania disebutkan dapat memperbaiki jaringan adiposa dan profil glukosa pada orang overweight atau obesitas. Tujuan: Studi literatur ini bertujuan untu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Consumption of olive oil, which serves as the main source of fat in MD, has been associated with numerous health benefits mediated by its antioxidant and anti-inflammatory properties. Uli et al demonstrated that the MD has the potential to effectively reduce LDL, TG, TC, and FBG levels while simultaneously increasing HDL-C concentrations in people with overweight and obesity [ 43 ]. A recent meta-analysis of 13 RCTs, investigating the comparative efficacy of the MD versus the conventional LFD on various metabolic outcomes among subjects at high cardiovascular risk who reside in non-Mediterranean regions, revealed that an MD improved TC levels.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of olive oil, which serves as the main source of fat in MD, has been associated with numerous health benefits mediated by its antioxidant and anti-inflammatory properties. Uli et al demonstrated that the MD has the potential to effectively reduce LDL, TG, TC, and FBG levels while simultaneously increasing HDL-C concentrations in people with overweight and obesity [ 43 ]. A recent meta-analysis of 13 RCTs, investigating the comparative efficacy of the MD versus the conventional LFD on various metabolic outcomes among subjects at high cardiovascular risk who reside in non-Mediterranean regions, revealed that an MD improved TC levels.…”
Section: Discussionmentioning
confidence: 99%
“…The role of MD in the modulation of lipid profiles has been evaluated in numerous systematic reviews and meta-analyses [ 20 , 56 , 57 , 58 , 59 ]. For example, Uli et al [ 57 ], in their systematic review, showed that MD could lower LDL, TGs, TC, and fasting blood glucose levels, while increasing HDL-C in overweight and obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The role of MD in the modulation of lipid profiles has been evaluated in numerous systematic reviews and meta-analyses [ 20 , 56 , 57 , 58 , 59 ]. For example, Uli et al [ 57 ], in their systematic review, showed that MD could lower LDL, TGs, TC, and fasting blood glucose levels, while increasing HDL-C in overweight and obese individuals. A recent review and meta-analysis of 13 RCTs analyzed the effectiveness of the MD versus a conventional low-fat diet on several metabolic outcomes, including markers of lipid profile, in subjects at high-risk living in non-Mediterranean countries.…”
Section: Discussionmentioning
confidence: 99%